Prevalence and aetiology of moderate and severe thrombocytopenia in a tertiary and quaternary centre in KwaZulu-Natal - Ayanda G. Jali; Bongani B. Nkambule (AOSIS, 2020)
Background: Thrombocytopenia is a common haematological disorder, characterised by platelet counts below 150 × 109/L. The aetiology of thrombocytopenia is multifactorial; notably, in a misdiagnosis this condition may be due to pre-analytical laboratory artefacts. Knowledge about the common aetiology of thrombocytopenia will assist clinicians in decision-making and interpretation of laboratory tests and this may lead to prompt, adequate patient management and cost-saving measures. Objective: This study determined the prevalence and aetiology of moderate and severe thrombocytopenia in a tertiary or quaternary laboratory in Durban, KwaZulu-Natal, South Africa. Methods: We conducted a retrospective study at the Inkosi Albert Luthuli Central Hospital haematology laboratory between October 2015 and April 2016. A total of 2076 full blood count results with a platelet count of less than 100 × 109/L were retrieved from the Inkosi Albert Luthuli Academic Hospital database. Laboratory data were extracted and matched with clinical data and used to identify the potential aetiology of thrombocytopenia. Results: The prevalence of thrombocytopenia was 14.9% within the selected study period. The haematology or oncology wards and clinic accounted for 55.2% of thrombocytopenia cases, whereas the adult and paediatric intensive care units accounted for 29.3%. Notably, 15.5% of thrombocytopenia cases were reported in non-haematology wards and clinics. The most common cause of thrombocytopenia was chemotherapy which accounted for 38.5% of all causes. Conclusion: In our tertiary and quaternary setting, thrombocytopenia in adults was most common in patients admitted to haematology and oncology wards. Moreover, chemotherapy-induced thrombocytopenia accounted for more than a third of all these cases.